Social Media Engagement of Saudi and Emirati Museums: A Comparative Study - Alharethi, Manasar (Department of Communications, Universitas Islam Indonesia, 2025)
With the broader use of social media channels by museums around the globe to engage their audiences, the nature of how cultural institutions in various regional settings utilize these technologies is critical to the communication theory. This study fills the gap of scholarly knowledge on the social media communication of museums in the Arabian Gulf as one of the regions that experience significant cultural and digital transformation due to the efforts such as Saudi Vision 2030 and the national innovation strategies of the UAE. This comparative case study has analysed the twitter/X interaction practices of three major museums: Twitter/X by Ithra (King Abdulaziz Center of world culture) located in Saudi Arabia, Twitter/X by Louvre Abu Dhabi and Twitter/X by the Museum of the Future (MOTF) in the UAE. The data was collected in September-October 2024 and analysed using mixed methods analysis, quantitative engagement and qualitative thematic content analysis. The research question focused on the implications of Twitter activities and content strategies of these museums on audience engagement in their respective institutional and cultural frameworks. The results show unique communication patterns which were influenced by institutional missions and cultural settings of the region. Ithra became the most active, having overall temporal distribution, and the highest level of activity. Louvre Abu Dhabi focused on dialogic communication via replies, whereas thread-based storytelling was favoured by MOTF in the stories of innovation. Thematic analysis shows that cultural approaches including the Arabic literature and Saudi heritage were prioritized by the @Ithra, the art and the cross-cultural dialogue became the priority of the @LouvreAbuDhabi, and technological innovation became the priority of the MOTF.